Binomial fibers and indispensable binomials. (May 2016) - Charalambous, Hara; Thoma, Apostolos; Vladoiu, Marius
Abstract: Let I be an arbitrary ideal generated by binomials. We show that certain equivalence classes of fibers are associated to any minimal binomial generating set of I . We provide a simple and efficient algorithm to compute the indispensable binomials of a binomial ideal from a given generating set of binomials and an algorithm to detect whether a binomial ideal is generated by indispensable binomials.